Coherent suppression of backscattering in optical microresonators - Svela, Andreas O.; Silver, Jonathan M.; Del Bino, Leonardo; Zhang, Shuangyou; Woodley, Michael T. M.; Vanner, Michael R.; Del'Haye, Pascal (Light: Science & Applications, 2020)
Optics: suppressing backscattering improves performance of microresonators A technique that suppresses backscattering in optical whispering-gallery-mode (WGM) microresonators significantly improves their performance, opening the door for their use in photonic devices for various applications. Imperfections in the microresonator surface or bulk material can cause backscattering of a portion of the light into the counterpropagating WGM, limiting their performance. A team of researchers led by Pascal Del'Haye from the Max Planck Institute for the Science of Light in Germany have now demonstrated a technique that can suppress backscatter by more than 30 decibels. By introducing an additional scatterer in the near-field of a high-quality-factor WGM microresonator, the researchers could control the scatterer's position so that the intrinsic and scatter-induced backpropagating fields interfere destructively. The technique could be used for photonic devices in which minimal backscattering is essential, such as laser gyroscopes and dual-frequency combs.
CRIS-Team WoS Importer:2021-01-15